Psychometric Properties of the Spanish Version of the Cognitive Flexibility Inventory - Irene Jaén; Verónica Vidal-Arenas; Carlos Suso-Ribera; M. Carmen Pastor; Azucena García-Palacios (Clínica y Salud. Investigación Empírica en Psicología)

(untitled)
Objective: Cognitive flexibility, identified as a transdiagnostic process in psychopathology, lacks specific Spanish-validated assessment tools. This study aims to examine the psychometric properties of the Cognitive Flexibility Inventory in a Spanish sample (N = 300, mean age = 22.66, SD = 4.92), 76% women). Method: An exploratory structural equation model (ESEM) was used to test the inventory’s latent structure. Reliability was calculated, as well as construct validity evidence with measures of emotion regulation, attributional style, and depression. Results: The original bifactorial model of the Cognitive Flexibility Inventory (Alternatives and Control scales) was replicated and obtained good fit indices. One item was excluded due to problematic factor loadings, yielding a final version with 19 items. Evidence of validity and reliability was obtained. Conclusions: The Spanish version of the Cognitive Flexibility Inventory showed satisfactory psychometric properties, making it a suitable measure for the assessment of cognitive flexibility in the Spanish population.